Tracing Unconfined Nearfield Spreading of a River Plume Interflow in a Large Lake (Lake Geneva): Hydrodynamics, Suspended Particulate Matter, and Associated Fluxes - Piton, Violaine; Soulignac, Frédéric; Lemmin, Ulrich; Graf, Benjamin; Wynn, Htet Kyi; Blanckaert, Koen; Barry, David Andrew (Frontiers in Water, 2022)
River inflows have a major influence on lake water quality due to their input of sediments, nutrients and contaminants. After leaving the river channel, river waters form a plume and interact with ambient lake waters. Strong hydrodynamic changes take place in the nearfield. To determine the nearfield hydro-sedimentary dynamics of the negatively-buoyant Rhône River plume in thermally stratified Lake Geneva, field campaigns were carried out at high and intermediate river discharge. High-resolution full-depth Acoustic Doppler Current Profiler (ADCP) transects were taken at 400, 800, 1200 and 1500 m from the river mouth, combined with profiles of temperature, turbidity and particle size distribution. These measurements provided, for the first time in a lake, detailed velocity fields across the full-plume cross-section in each transect. Furthermore, the unique combination of measurement techniques allowed the quantification of entrainment, Suspended Particulate Matter (SPM) concentrations and fluxes. They revealed that the negatively buoyant river inflow intruded into the metalimnion as a laterally unconfined interflow and continued flowing straight out in the streamwise direction, since currents in the lake were weak. At the same time, it mainly spread laterally due to entrainment of ambient water. The size of the interflow core and its velocity progressively decreased with distance from the mouth, as did SPM concentrations and volumes of particles (by a factor of 2-3 within 1500 m), due to sediment settling and entrainment. The interflow momentum flux remained constant along the pathway, but interflow cross sections and discharge increased 2-3 times (within 1500 m). The entrainment coefficient was > 2 at 400 m and further increased nonlinearly along the pathway. These values are much higher than those reported for laterally confined laboratory studies. The particle size distribution in the interflow was dominated by fine particles (< 32 μm), which were transported up to 1500 m from the mouth and most likely beyond, whereas larger particles (> 62 μm) almost completely settled out before reaching that distance. The above processes occurred independent of river discharge; their intensity, however, changed with discharge.